Development of extensive growth and growth boundary models for mesophilic and psychrotolerant Bacillus cereus in dairy products (Part 1) - Maryam Maktabdar; Ellen Wemmenhove; Elissavet Gkogka; Paw Dalgaard (Frontiers in Microbiology)
Guidelines for combinations of product characteristics to prevent unacceptable growth of Bacillus cereus in foods are lacking, and models are therefore valuable for predicting these responses. B. cereus isolates of dairy origin were used to generate a comprehensive dataset to develop two cardinal parameter growth and growth boundary models for mesophilic and psychrotolerant B. cereus, respectively. Each model incorporated the inhibitory effect of 11 environmental factors, i.e., temperature, pH, NaCl/aw, organic acids (acetic, benzoic, citric, lactic, and sorbic), phosphate salts (orthophosphate, diphosphate, and triphosphate), and the effect of interactions between these factors. Cardinal parameter values for mesophilic and psychrotolerant strain cocktails were estimated using 231 and 203 maximum specific growth rates (μmax values), respectively, generated in a standard liquid laboratory medium (BHI broth). Furthermore, an additional 113 and 100 μmax values were generated for the two strain cocktails using a dairy-specific liquid medium (an ultra-filtration permeate from whey) to evaluate growth responses obtained in BHI broth. Cardinal parameter values for the two extensive growth boundary models were selected conservatively using data from BHI broth or UF permeate, such that the widest growth range was obtained for each environmental factor. The studied cocktail of six vegetative mesophilic B. cereus isolates exhibited greater acid tolerance in UF permeate than in BHI broth with lower pHmin (pHmin values of 4.75 versus 4.98), higher minimum inhibitory concentrations (MIC) of undissociated lactic acid (MICu,LAC of 2.99 versus 2.34 mM) and total citric acid (MICT,CAC of 169.1 versus 82.5 mM). The psychrotolerant B. cereus strain cocktail also had lower pHmin and higher values for MICLAC and MICT,CAC in UF permeate than in BHI broth. The remaining cardinal parameter values were determined from growth rates in BHI broth. The two new models can predict the combined effect of storage temperature and a wide range of dairy product characteristics, including combinations of organic acids and phosphate melting salts. These growth and growth boundary models can support the evaluation and management of the two B. cereus subgroups in various dairy products. However, product validation of the two predictive models is required to determine their performance and range of applicability.